Tourism and its future: tourism development strategies in the context of coast, culture and agriculture-Meander Basin - Koç Ercan; Gözdem Aysu; Ayşe Nur Ökten; Betül Şengezer (European Regional Science Association (ERSA), 2011)
Turkey, during nearly in a hundred years of development period have lived a process where population and income in rural areas have decreased but on the contrary urban and coastal areas have developed. Now, one of every four people live in urban settlements. During this process, the living environment and the quality of life has negatively effected by the concentration of the urban areas not as the planning has foreseen, the concretion of urban surfaces and insufficient reinforcement area problems. The naturalness of the rural areas, product diversity, open space, the relations of production, rural culture and lifestyle has become longed qualifications. Büyükmenderes basin with its nature of accessibility, integrity of coastal-plain-mountain where combined, different geographies, naturalness, rich fauna and flora, the sea, lakes, rivers, hot springs, special products, historical values and cultural diversity has a special place. At the same time the country's most important coastal tourism are the focus of the surface of the rear axle Ku?adas?-Bodrum. Increase in the density of urban settlements, inadequate reinforcement measures and the loss of legibility, rural poverty and abandonment of settlements inhabited by the problems of this scope requires new improvements and the development of new principles of sustainability. In this context Büyükmenderes basin is in great potential. To participate in the production process, nature sports facilities, health tourism through thermal resources, cultural tourism, access to a rich diversity of fauna and flora, opportunities provided by sea, lake, river sources, the local culture, lifestyle, recognition of settling relations, accommodation with local properties for the region will take different roles at all levels and contains programmability. In this study, such urban settlements like Aydin, Soke specified in the above content, for Büyükmenderes basin development and promotion strategies will be examined for the integrity of coastal tourism, culture, agriculture and a proposal of a model will be developed.
Keywords: 330